2004
DOI: 10.4315/0362-028x-67.11.2578
|View full text |Cite
|
Sign up to set email alerts
|

Observation Versus Self-Report: Validation of a Consumer Food Behavior Questionnaire

Abstract: A reliable and validated set of food safety behavior questions that could be used with confidence when evaluating food safety education programs was identified in this study. A list of 29 food-handling and consumption behaviors rank-ordered within five pathogen control factors by nationally recognized food safety experts was the basis for the development of the behavior questions. Questions were evaluated for reliability and several forms of validity. During a kitchen activity session, 70 graduates of a nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 18 publications
9
61
0
Order By: Relevance
“…This is consistent with the literature that has shown consumers do not always follow recommended food safety practices when preparing hamburgers (Phang and Bruhn, 2011). Studies have found limited use of thermometers by consumers when preparing food at home; one observational study found that only 4%Á15% of participants used thermometers when preparing hamburgers for personal consumption (Anderson et al, 2004;Kendall et al, 2004;Phang and Bruhn, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…This is consistent with the literature that has shown consumers do not always follow recommended food safety practices when preparing hamburgers (Phang and Bruhn, 2011). Studies have found limited use of thermometers by consumers when preparing food at home; one observational study found that only 4%Á15% of participants used thermometers when preparing hamburgers for personal consumption (Anderson et al, 2004;Kendall et al, 2004;Phang and Bruhn, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…They were also assured that their names and wordings would not be revealed to anyone other than the research team. Moderator's guide was designed based on the research objectives (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), which consisted of a series of open-ended questions to allow the respondents to explain their own opinions and experiences (Table 1). Each team consisted of one moderator, one observer and two note-takers.…”
Section: Methodsmentioning
confidence: 99%
“…Survey items originated from previous studies [29][30][31][32] and were tested with five key informants for content and face validity. The online version of the survey was developed using SelectSurvey.NET (ClassApps, Release 2.0, Overland Park, KS, USA).…”
Section: The Surveymentioning
confidence: 99%